1977
DOI: 10.1136/vr.101.10.181
|View full text |Cite
|
Sign up to set email alerts
|

Long term results of excision arthroplasty of the canine hip

Abstract: An analysis has been made of the long term results of excision of the canine femoral head and neck. The most frequent postoperative findings include shortening of the operated limb and restricted movement of the hip pseudarthrosis. Although few dogs show lameness or pain in the operated hip, muscle atrophy is a frequent finding even after eight years. Difficulty in jumping and in climbing stairs are more commonly found postoperatively in the larger breeds of dog. Despite these noted abnormalities almost all ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
3

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 0 publications
5
65
0
3
Order By: Relevance
“…This corresponds to the typical mushroom shape that appears in the course of the disease 23–27 . The femoral heads in dogs with coxofemoral luxation were characterized by a regular trabecular structure and preserved contours, as expected 28,29 …”
Section: Discussionsupporting
confidence: 54%
“…This corresponds to the typical mushroom shape that appears in the course of the disease 23–27 . The femoral heads in dogs with coxofemoral luxation were characterized by a regular trabecular structure and preserved contours, as expected 28,29 …”
Section: Discussionsupporting
confidence: 54%
“…Montgomery et al reported a trend toward higher mean body weight in dogs with lameness following exercise after FHO 15 . Duff and Campbell reported that 50% of dogs that had FHO had residual muscle atrophy of the operated limb and 69% had shortening of that limb 16 . They also reported 22% of dogs were lame after exercise and 20% had signs of pain on manipulation of the operated joint.…”
Section: Discussionmentioning
confidence: 99%
“…ALTHOUGH pelvic fractures are common in small animals, with a reported incidence of up to 25 per cent of all fractures, they occur infrequently in horses (Vaughan 1965;Duff and Campbell 1977;Denny 1978;Jeffcott 1982). Despite this, most equine practitioners are, at some time, faced with making a diagnosis, formulating a prognosis and recommending therapy for horses with a pelvic fracture.…”
Section: Introductionmentioning
confidence: 99%